Self-reported characterization of sleep quality in trained male and female amateur triathletes: a descriptive study - Luiz Vieira da Silva Neto; Tatiana Albuquerque Melo Kramer; Gloria Maria Alves Trajano; Luiz José Frota Solon Júnior (Pensar en Movimiento)
Sleep quality is a determining factor for performance and health of sportspeople in general. The objective of the present study was to characterize sleep quality in trained male and female amateur triathletes aged between 20 and 59 years. A survey was carried out with 151 trained amateur triathletes, 108 men (38.6 ± 8.1 years; 5.8 ± 4.3 years’ experience in triathlon training; training frequency 6.3 ± 0.9 days per week) and 43 women (39.3 ± 7.6 years; 4.8 ± 3.3 years’ experience in triathlon training; training frequency 6.5 ± 0.6 days per week). Sleep quality was measured through the Pittsburgh-Br Sleep Quality Index (PSQI-Br). Total values under 05 points indicate sleep quality is good, and values equal to or above 05 points indicate poor sleep quality. Sub-scale data were analyzed by using absolute and relative frequencies. The remaining data for characterizing sleep quality were analyzed with median, mean, standard deviation, standard error and a confidence interval of 95% of the mean. Both male and femaletriathletes have poor sleep quality (values equal to or above 05 points), which can have negative effects on health and performance. In conclusion, all athletes, regardless of gender and age group, have poor sleep quality.